Distribution and Variation of Mining-Induced Stress in the Reverse Fault-Affected Coal Body - Rui Zhou; Yujin Qin; Zhizhen Zhang (Advances in Civil Engineering)
This study aimed to explore the stress distribution and variation of reverse fault-affected mined coal body. A mechanical analysis model of the coal body in the reverse fault area was first established, then the coal body stress characterization equation was derived, and the stress distribution pattern on the coal body was calculated. Subsequently, applying the Mohr–Coulomb strength criterion revealed the following relationship: the closer is the distance to the reverse fault, the worse is the stability of the coal body, and that the coal body strength influences the stress concentration of the coal body in front of the working face. Moreover, simulation with FLAC3D was carried out to verify the coal body stress calculated by the mechanical model as well as the fluctuation of the coal body stress concentration. It could be concluded that while mining the hanging wall of the reverse fault, the stress concentration of mined coal body decreases with the increase of reverse fault dip angle, but increases with the increase of reverse fault throw; the stress concentration magnitude generated during footwall mining is lesser than that during hanging-wall mining. In other words, the magnitude of coal body stress concentration can be affected by the hanging wall and footwall mining, as well as parameters of the reverse fault. Finally, intrinsically safe GZY25 borehole stress sensors were used to monitor the coal body stresses in the reverse fault area under the influence of mining in Xinchun Coal Mine and ZuoQiuka Coal Mine. It was found that the coal body stress concentration in front of the working face either increased gradually or increased first before decreasing. It can be concluded that with the decrease of the distance between the working face and reverse fault, the vertical stress of the coal body increases, and the vertical stress of the coal body begins to increase obviously at a certain position. At this point, the vertical stress of the coal body can be generalized to 1.02–1.39 times of the initial vertical stress. Furthermore, the stress concentration coefficient of coal body is related to the distance from the reverse fault, and two changes occur: ① if the coal-bearing capacity does not exceed its strength, the coal stress in front of the working face increases gradually, and the stress concentration factor increases gradually; ② the stress concentration coefficient of mining coal body increases first, such that when the coal body bearing capacity exceeds its strength, the coal body fails and loses all its effective bearing capacity, followed by the decrease in coal body stress concentration coefficient.